Probing the role of the C2F domain of otoferlin - Chen, Han; Fang, Qinghua; Benseler, Fritz; Brose, Nils; Moser, Tobias (Frontiers in Molecular Neuroscience, 2023)
Afferent synapses of cochlear inner hair cells (IHCs) employ a unique molecular machinery. Otoferlin is a key player in this machinery, and its genetic defects cause human auditory synaptopathy. We employed site-directed mutagenesis in mice to investigate the role of Ca2+ binding to the C2F domain of otoferlin. Substituting two aspartate residues of the C2F top loops, which are thought to coordinate Ca2+-ions, by alanines (OtofD1841/1842A) abolished Ca2+-influx-triggered IHC exocytosis and synchronous signaling in the auditory pathway despite substantial expression ( 60%) of the mutant otoferlin in the basolateral IHC pole. Ca2+ influx of IHCs and their resting membrane capacitance, reflecting IHC size, as well as the number of IHC synapses were maintained. The mutant otoferlin showed a strong apex-to-base abundance gradient in IHCs, suggesting impaired protein targeting. Our results indicate a role of the C2F domain in otoferlin targeting and of Ca2+ binding by the C2F domain for IHC exocytosis and hearing.